Clinical management of chronic mesenteric ischemia - van Dijk, Louisa JD (United European Gastroenterol J, 2018)
This review provides an overview on the clinical management of chronic mesenteric ischemia (CMI). CMI is defined as insufficient blood supply to the gastrointestinal tract, most often caused by atherosclerotic stenosis of one or more mesenteric arteries. Patients classically present with postprandial abdominal pain and weight loss. However, patients may present with, atypically, symptoms such as abdominal discomfort, nausea, vomiting, diarrhea or constipation. Early consideration and diagnosis of CMI is important to timely treat, to improve quality of life and to prevent acute-on-chronic mesenteric ischemia. The diagnosis of CMI is based on the triad of clinical symptoms, radiological evaluation of the mesenteric vasculature and if available, functional assessment of mucosal ischemia. Multidisciplinary consensus on the diagnosis of CMI is of paramount importance to adequately select patients for treatment. Patients with a consensus diagnosis of single-vessel or multi-vessel atherosclerotic CMI are preferably treated with endovascular revascularization.